(untitled) (Revista Brasileira Multidisciplinar, 2010)
Most problems of public school come from a fragmented teaching vision, obsolete methodologies, an inflexible curriculum, teachers as transmitters of an unquestionable science and students who are depositary of this content. All these aspects are products of the worldview originated from classical science. As a counterpoint to this paradigm in education, derived from the classical science, another is being built, whose foundation is based mainly on the Theory of Relativity, on the Quantum Theory and on the Dissipative Structures Theory. It involves a live educational process, in which the student is not limited to be only a content receiver, but to construct knowledge with peers and their teacher, who becomes the facilitator of a transitory knowledge. The aim of this study is to analyze, by means of a literature review, the implications of the old and the new scientific paradigms for education.